Product Innovation: A Multimodal Interaction Design Method based on HCI and TRIZ. Issue 1 (April 2021) - Chen, Shaohan; Kamarudin, Khairul Manami; Yan, Shihua
Abstract: The border between tangible and digital products is getting more diffuse, which has caused the focus of product innovation to migrate from technology to user experience and Human-Computer Interaction (HCI). In HCI, the comprehensive interactions between users and products are collectively referred to as multimodal interaction, and multimodal interaction defines the user experience of the product. However, there is currently a lack of design methods for multimodal interaction. This paper presents a multimodal interaction design method by exploiting the synergy of HCI and TRIZ. This method covers the whole design process, from the analysis of the user needs to the generation of the design solutions and it contains tools as flexible as active, a more valid view on user experience is provided during all design stages. A case experiment validated the effectiveness of the method. The implications of this study will help designers to innovate products with multimodal interaction.